The failure of the founding fathers : Jefferson, Marshall, and the rise of presidential democracy - Ackerman, Bruce A. (Belknap Press of Harvard University Press, 2007)
Describes previously unknown aspects of the electoral college crisis of 1800, presenting a revised understanding ofthe early days of two great institutions that continue to have a major impact on American history: the plebiscitarian presidency and a Supreme Court that struggles to put the presidency's claims of a popular mandate into constitutional perspective. Through close studies of two Supreme Court cases, Ackerman shows how the court integrated Federalist and Republican themes into the living Constitution of the early republic. The ink was barely dry on the Constitution when it was almost destroyed by the rise of political parties in the United States. As Bruce Ackerman shows, the Framers had not anticipated the two-party system, and when Republicans battled Federalists for the presidency in1800, the rules laid down by the Constitution exacerbated the crisis. --